Making globalization work - Stiglitz, Joseph E. (London, 2006)
In Globalization and its Discontents Joseph Stiglitz changed the views of the public and world leaders alike by showing why globalization doesn't work for the world's poor. In this bold, ambitious follow-up, Stiglitz shows how powerful organizations such as the UN, the IMF and the World Bank can be made to consider everyone's interests. Stiglitz examines how change has occurred rapidly over the past four years, proposing solutions and looking to the future. He puts forward radical new solutions to the seemingly intractable international problems which we face - in forms that are more likely to be accepted both by the US and the developing world than previous proposals. Another world is possible, he argues, and is not only morally right, but of benefit to us all.
Keywords: Economic development